Clinical Reasoning: A 50-Year-Old Man With Intracerebral Hemorrhage and Tortuous Retinal Arterioles - Bouchart, Jean; Weber, Sacha; Coste, Thibault; Laville, Marie-Alice; Loisel, Margaux; Nehme, Ahmad (Neurology, 2024)
A 50-year-old man presented with headache. Examination showed left sided ataxic hemiparesis and elevated blood pressure. Brain imaging revealed an acute intracerebral hemorrhage in the right lentiform nucleus, deep and periventricular white matter hyperintensities, and predominantly deep cerebral microbleeds. Fundus examination showed important arteriolar tortuosity involving several blood vessels. In this young patient, we explain the diagnostic approach to intracerebral hemorrhage, the causes of cerebral small vessel disease, and the interpretation of biomolecular tests.